The civil society as a territory of resistance and defense, Bosnia-Herzegovina and the former Yugoslavia». A personal testimonial - Masic, Alma (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This is a direct testimonial of what occurred in the former Yugoslavia during the 1990s. It is difficult to write a scientific article on the matter, therefore, the intention is not to analyze, elaborate or demonstrate certain deeds, but on the contrary, it aims to put forward the experiences of people who, while being at war, tried to document the events as they took place, present relevant facts, and information in order to better understand what was happening and transmit this to a wider audience, especially the young. This writing intends to show how the members of the civil society and other relevant institutions, formal and informal, individual and collective, oppose to the relativization of what happened and the abuse on the part of nationalism of historical events and the politicizing of the victims and the problems with justice. As future decision-makers in the countries of the former Yugoslavia, the young must and have the right to know what happened in the nineties, because it is they who will have to make sure that it does not happen again. Above all, this article depicts the life of an «ordinary» person who finds himself in the middle of extraordinary circumstances, trying to do good for his fellow citizens.